No 'self' left behind? Part-time distance learning university graduates: social class, graduate identity and employability. (1st September 2016) - Delaney, Lorraine; Farren, Margaret
Abstract: Higher education (HE) is regarded as a pathway to upward social mobility for those from lower socio-economic backgrounds. Social mobility is itself seen as important both for individual and national prosperity and is a key driver of government funding for HE. While access to HE has substantially increased over the past number of years, the evidence suggests that social inequalities continue to be reproduced, with working-class students more frequently accessing lower status institutions and courses. This in turn can impact negatively on their labour market outcomes. This paper offers a critical appraisal on the employability discourse. Drawing on a survey of 268 distance graduates from an Irish university, together with 5 individual interviews, findings indicate that distance graduates are likely to be from lower socio-economic backgrounds and have delayed participation in university education for reasons relating to social class. Although mostly in employment, they are motivated to participate in HE by their concerns regarding their long-term employability. The literature identifies that our employability is something we negotiate with others. This paper posits that, for distance graduates, in addition to this process of convincing others, the graduate must also convince themselves of the value of their own achievement. Transitioning to graduate employment, and developing a graduate identity, can therefore be a slow internal and external process of negotiation.